Cloudy with a chance of meatballs - Barrett, Judi.; Barrett, Ron (New York : Atheneum, 1978)
Life is delicious in the town of Chewandswallow where it rains soup and juice, snows mashed potatoes, and blows storms of hamburgers--until the weather takes a turn for the worse.
3.7
K-3
K-3
Elem. School Library Collection
Book Links (A.L.A.)
Booklist
Keywords: Weather -- Fiction; Food -- Fiction; Weather -- Fiction; Food -- Fiction; Humorous fiction